The results of surgical decompression in the treatment of foot drop due to peroneal nerve entrapment after bariatric surgery - Lale, Azmi; Kirkil, Cuneyt; Ozturk, Sait; Yur, Mesut; Can, Omer Faruk; Artas, Gokhan; Aygen, Erhan (Elsevier Science Inc, 2020)
Background: The loss of the fat pad surrounding the fibular head after rapid and excessive weight loss after bariatric surgery can lead to foot drop symptoms due to peroneal nerve entrapment (PNE). Conservative and surgical approaches have been described for the treatment of this condition, but there is some controversy over the effectiveness of the treatment modalities. Objective: We aimed to investigate the causes and frequency of foot drop due to PNE after bariatric surgery and to investigate the effects of peroneal nerve decompression (PND) as a surgical treatment for PNE. Setting: Single center, university surgical department. Methods: We retrospectively evaluated a series of 2607 patients in terms of neurologic complications after bariatric surgery. Patients' age, sex, co-morbid diseases, vitamin and electrolyte levels, body mass index and postoperative excess weight loss, affected limb, duration of symptoms, and muscle strength scores (according to the Medical Research Council scale) were recorded. Results: A total of 14 (.5%) patients had foot drop symptoms due to PNE. Of these patients, 9 underwent PND. The mean excess weight loss of PND patients at postoperative months 6 and 12 were 68.8 +/- 13.5 and 100.9 +/- 10.8, respectively. Foot drop symptoms became evident 5 to 11 months after bariatric surgery, affecting only a unilateral lower extremity in all patients. In laboratory analysis, there were no signs of nutritional and vitamin deficiency or insufficiency in any of the PND cases. Muscular strength was Medical Research Council grade 0 in all patients. The median duration of symptoms was 9 days, and the median complete recovery time was 40 days after PND. Patients who had a duration of symptoms for a maximum of 12 days were completely healed 30 days after PND. Conclusion: PND should be the first-choice treatment procedure for acute foot drop due to PNE after bariatric surgery. (C) 2020 American Society for Bariatric Surgery. Published by Elsevier Inc. All rights reserved.
Keywords: Foot drop; Neurologic complications; Obesity surgery; Peroneal nerve decompression; Peroneal nerve entrapment